VD_FINDINFO Arrêt / 2014 / 639 vom 6. August 2014 - VD Tribunal cantonal (2014)
REJET DE LA DEMANDE, SURVEILLANCEEN GÉNÉRAL, RETRAIT DU DROIT DE GARDE, AUDITION DE L'ENFANT | 307 al. 3 CC, 310 al. 1 CC, 314a al. 1 CC, 450 CC